Swedish teachers' perspectives on parental involvement in children's early learning of number - Löwenhielm, A; Marschall, G; Sayers, J; Andrews, P (Nordic Society for Research in Mathematics Education, 2017)
In this paper, we present results of an interview study of Swedish teachers’ views on parental involvement in year one children’s learning of number. Interview transcripts were subjected to a data-driven inductive analysis that identified two broad categories of parental involvement which, according to teachers, may have influence on children’s learning of number. Firstly, there were indirect involvements concerning the ways in which parents convey messages, both positive and negative, about school and mathematics in general. Secondly, there were direct number-related practices, falling into two broad categories. The first of these concerned formal activities, such as homework, which tended to dichotomise teachers. The second, largely hypothetical, concerned the exploitation of everyday informal situations and number-related games with the potential to facilitate children becoming friends with numbers.